2019
DOI: 10.1080/19491034.2019.1603093
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive nuclear proteome of Arabidopsis obtained by sequential extraction

Abstract: In eukaryotes, the nucleus plays key roles in fundamental cellular processes, including DNA replication, chromatin maintenance, transcription, and translation. To better understand the functional diversity of nuclei, we developed a method for the comprehensive extraction of the nuclear proteome from Arabidopsis. We used a buffer with a high sucrose concentration to purify nuclei and then conducted solubility-based fractionation to increase proteome coverage. We identified 1539 proteins and two novel nuclear en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 81 publications
2
20
0
Order By: Relevance
“…PL of FAMA-expressing nuclei and comparison with a general nuclear proteome in our 'nuclear proteome' experiment showed that TID is suitable to capture sub-cellular proteomes at a cell type-specific level, even when the cell type is rare. We identified 1,618 proteins in both nuclear datasets combined, which is comparable to the most recent nuclear proteome obtained from cultured Arabidopsis cells (Goto et al 2019). Judging from experimentally determined and predicted localization of the identified proteins and functional annotation with GO analysis, we obtained high specificity for nuclear proteins and identified proteins from all major nuclear subdomains.…”
Section: Suitability Of Turboid and Miniturboid For Application In Plsupporting
confidence: 60%
See 2 more Smart Citations
“…PL of FAMA-expressing nuclei and comparison with a general nuclear proteome in our 'nuclear proteome' experiment showed that TID is suitable to capture sub-cellular proteomes at a cell type-specific level, even when the cell type is rare. We identified 1,618 proteins in both nuclear datasets combined, which is comparable to the most recent nuclear proteome obtained from cultured Arabidopsis cells (Goto et al 2019). Judging from experimentally determined and predicted localization of the identified proteins and functional annotation with GO analysis, we obtained high specificity for nuclear proteins and identified proteins from all major nuclear subdomains.…”
Section: Suitability Of Turboid and Miniturboid For Application In Plsupporting
confidence: 60%
“…Importantly, chloroplast proteins, which are a major source of contamination in plant MS experiments, make up only about 3 % of our identified proteins (source fileFigure 6supplemental table 5). In contrast, about 12 % and 6 % of the proteins identified in the two most recent Arabidopsis nuclear proteome studies(Palm et al 2016;Goto et al 2019), are predicted to be in the chloroplast (SUBAcon prediction, SUBA4). Gene ontology (GO) analysis is also consistent with nuclear enrichment in both nuclear TID datasets (Figure 6figure supplement 3, source file Figure 6supplemental tables 2,3 and 7).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…To estimate how ‘pure’ our nuclear proteomes are, we curated published nuclear and subnuclear compartment proteomes (Bae et al, 2003; Bigeard et al, 2014; Calikowski et al, 2003; Chaki et al, 2015; Palm et al, 2016; Pendle et al, 2005; Sakamoto and Takagi, 2013; Goto et al, 2019) and searched the Arabidopsis protein subcellular localization database SUBA (version 4, Hooper et al, 2017, http://suba.live/) for proteins that were observed in the nucleus as fluorescent-protein fusions. This resulted in a combined list of 4,681 ‘experimentally determined nuclear proteins’; 4021 from MS and 975 from localization studies (Supplementary file 3 – Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Chloroplast proteins, which are a major source of contamination in plant MS experiments, make up only about 4% of our identified proteins based on experimental and prediction data (Supplementary file 3 – Table 5). For a comparison, about 12% and 6% of the proteins identified in the two most recent Arabidopsis nuclear proteome studies (Palm et al, 2016; Goto et al, 2019), are predicted to be in the chloroplast (SUBAcon prediction, SUBA4). Gene ontology (GO) analysis is also consistent with nuclear enrichment in both nuclear TbID datasets (Figure 6—figure supplement 4, Supplementary file 3 – Tables 2, 3 and 7).…”
Section: Resultsmentioning
confidence: 99%